Structural, dielectric and electrocaloric properties in lead-free Zr-doped Ba0.8Ca0.2TiO3 solid solution. (July 2016) - Asbani, B.; Gagou, Y.; Dellis, J.-L.; Lahmar, A.; Amjoud, M.; Mezzane, D.; Kutnjak, Z.; El Marssi, M.
Abstract: We investigate in the present work the additional data points ( x =0.02, 0.06 and 0.08) to the previous reported paper (Asbani et al., 2015) [21] that sufficiently enrich to understand the EC properties and underlying phase diagram of the lead-free Ba0.8 Ca0.2 Ti(1− x ) Zr x O3 ( x BCTZ) system. X-ray diffraction analysis performed at room temperature, confirms a continuous tetragonal solid solution with P 4 mm (No. 99) space group that evolved to pseudo-cubic symmetry for the high Zr-content compounds. Ferroelectric and paraelectric behaviors were highlighted using P–E hysteresis data versus temperature. Phase transition was confirmed by dielectric permittivity measurements versus temperature showing a decrease of the Curie temperature when Zr-content increases. From P–E hysteresis recording the electrocaloric temperature change (Δ T ) was calculated that ranged in between 0.12 and 0.27 K and the electrocaloric responsivity ( ξ ) in 0.15 to 0.34×10 −6 K·m/V under 7.95 kV/cm applied electric field. The zero-field entropy is compared to electrocaloric isothermal entropy to estimate the extent the EC is being under-driven.